Land access, livelihoods, and dietary diversity in a fragile setting in northern Uganda - Kang, Yunhee; Ganganaboina, Sarika; Fang, Theresa; Tran, Andy; Suzuki, Aki; Son, Jeongeun; Roh, Kyunghoo (Frontiers in Sustainable Food Systems, 2023)
Food systems in fragile contexts are hardly investigated. We examined the crop value chain activities, agriculture income, coping strategy, and food consumption score (FCS) among South Sudan refugees (n=394; refugee HH) and Uganda host communities (n=420; host HH) living on the northern border of Uganda. Secondary data analysis was conducted using baseline data collected from an NGO-supported project. Linear regression analysis was conducted to test the association between the type of crop for growing and selling, agriculture income, coping strategy, and FCS in the refugee HH and host HH, separately. The mean number of growing and selling crops was 2.7 (SD 1.7) and 0.6 (1.0) in the refugee HH and 3.6 (1.4) and 1.3 (1.1) in the host HH. Overall food insecurity and FCS was poor in both refugee and host HH. Larger land access was associated with diverse crop production and crop selling in both groups (p<0.05). The greater number of crop types grown was marginally associated with FCS in host HH only (β=1.00; p=0.05). Selling more types of crops was associated with agriculture income in both groups (p<0.05) and was not related to rCSI in either group, but marginally associated with FCS among only host HH (β=0.84; p=0.04). An inequitable food system existed between the host community and South Sudan refugees residing on the northern border of Uganda. The findings suggest that diversifying crops for selling and enhancing marketing channels could aid both host and refugee communities in establishing resilient food systems.